Inflammation triggered by the NLRP3 inflammasome is a critical driver of diabetic bladder dysfunction - Hughes, Francis M.; Odom, Michael R.; Cervantes, Anissa; Purves, J.Todd (Frontiers in Physiology, 2022)
Diabetes is a rapidly expanding epidemic projected to affect as many as 1 in 3 Americans by 2050. This disease is characterized by devastating complications brought about high glucose and metabolic derangement. The most common of these complications is diabetic bladder dysfunction (DBD) and estimates suggest that 50-80% of patients experience this disorder. Unfortunately, the Epidemiology of Diabetes Interventions and Complications Study suggests that strict glucose control does not decrease ones risk for incontinence, although it does decrease the risk of other complications such as retinopathy, nephropathy and neuropathy. Thus, there is a significant unmet need to better understand DBD in order to develop targeted therapies to alleviate patient suffering. Recently, the research community has come to understand that diabetes produces a systemic state of low-level inflammation known as meta-inflammation and attention has focused on a role for the sterile inflammation-inducing structure known as the NLRP3 inflammasome. In this review, we will examine the evidence that NLRP3 plays a central role in inducing DBD and driving its progression towards an underactive phenotype